2017
DOI: 10.9734/arjom/2017/33023
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception and Its Impact on Ghanaian Students’ Interest in Mathematics: Multivariate Statistical Analytical Approach

Abstract: The study aims at addressing the effect of students' perception and its impact on student interest in Mathematics using multivariate statistical techniques. One Thousand Two Hundred and Sixty Three (1263) students were drawn from ten (10) Senior High Schools in the Ashanti region of Ghana using structured questionnaires to investigate the effect and impact of student perception on their interest in Mathematics. The study used multivariate techniques to investigate and further predict the effect and impact of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 21 publications
5
19
0
Order By: Relevance
“…The constructs exhibited direct and significant relationship between students' motivation on students' interest in mathematics as well as students' perception about mathematics on student interest in mathematics. The results was consistent with other earlier studies [18,19,46]. The results suggest that the more positively students perceive mathematics, the better their interest in mathematics.…”
Section: Discussion Of Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The constructs exhibited direct and significant relationship between students' motivation on students' interest in mathematics as well as students' perception about mathematics on student interest in mathematics. The results was consistent with other earlier studies [18,19,46]. The results suggest that the more positively students perceive mathematics, the better their interest in mathematics.…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…Students' interest in mathematics is significantly influenced by the students' perception about mathematics. These studies have shown that the more positive perception students' have about mathematics, the more interest they demonstrate in mathematics, hence positive perception about mathematics results in high interest in mathematics [18,19].…”
Section: Students' Perception and Attitude On Interestmentioning
confidence: 99%
“…Students who considered mathematics positively inclined to give more attention and listen carefully to the explanation given by the teacher during the mathematics sessions than those who had negative thinking. This finding is in the light of research by Arthur et al (2017) that students' negative perspectives on mathematics significantly influence their low interest in participating during mathematics learning.…”
Section: Discussionsupporting
confidence: 65%
“…Attitude in terms of patience, confidence, willingness and anxiety help in problem solving in mathematics achievement. However, student's perception has created a bad public image describing mathematics as difficult, abstract, theoretical and not an interesting subject according to Arthur, Asiedu-Addo and Assuah (2017). Attitudes determine student's ability and willingness to learn a course or work on a variety of assigned tasks available.…”
Section: Background To the Studymentioning
confidence: 99%